Вимоги до математичного забезпечення балансуючого ринку електричної енергії України - Блінов, І.В.; Парус, Є.В. (Технічна електродинаміка, 2012)
The basic requirements and features of software of the automated information system for the operator of the electricity balancing market in Ukraine are given. The requirements to the problem solving of a competitive selection of resources, system of restrictions and to the problem solving of the electricity balancing market taking into account technological features of generators, which are the participant of the balancing market are defined.